Addressing Cancer Screening Inequities by Promoting Cancer Prevention Knowledge, Awareness, Self-Efficacy, and Screening Uptake Among Low-Income and Illiterate Immigrant Women in France - Maria De Jesus; Maria De Jesus; Maria De Jesus; Christelle M. Rodrigue; Sarah Rahmani; Christian Balamou (Frontiers Media S.A., 2021)
Objective: Cancer screening rates are suboptimal for disadvantaged populations in France, yet little evidence exists on their cancer-related knowledge and screening barriers. The main objective of this study was to examine cancer-related knowledge, awareness, self-efficacy, and perceptions of screening barriers among low-income, illiterate immigrant women in France following an 8-weeks cancer educational intervention.Methods: Semi-structured qualitative interviews were conducted with 164 female participants in the Ain department of France between January 2019 and March 2020. Adopting the Health Belief Model as an intervention and analytic framework, salient themes were identified using qualitative thematic analysis.Results: Increased levels of perceived susceptibility to and perceived severity of cancer contributed to higher motivation to get screened. Barriers to screening included low French proficiency, shame surrounding illiteracy, and constant worries due to precarious living conditions. Perceived benefits (e.g., valuing one's health and health-promoting behaviors), cues to action from a trusted source, and greater self-efficacy (e.g., more autonomous in healthcare-seeking) outweighed perceived barriers, including cultural barriers.Conclusions: Implications include developing audience-responsive targeted cancer screening communication strategies and educational materials to increase screening rates and reduce cancer and cancer screening inequities.